PENGARUH KOMPENSASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN UNIVERSITAS TRIDINANTI PALEMBANG - Firdaus Sianipar; Zumiro . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
This study aims to determine the effect of Compensation, Motivation and Work Discipline on Employee Performance at the University of Tridinanti Palembang. Both partially and jointly. In this study the total population was 70 people, with details of 35 trial samples and 35 research samples. From the results of the study obtained the variable Compensation regression coefficient (X1) of 0.147, Motivation (X2) 0.135, Work Discipline (X3) 0.155 and also produces a constant value of 38.496 so the Multiple Linear Regression equation is as follows: Y = 38.496 + 0.147 X1 + 0.135 X2 + 0.155 X3, while the correlation coefficient results are 0.6343 which means it has a very strong relationship between the independent variable and the dependent variable, also the determination coefficient (R2) of 0.320 This value can be interpreted that the percentage effect of Compensation, Motivation and Work Discipline on Performance is 32% while the remaining 78% is influenced by other variables not included in this study.Keywords: compensation, motivation, work discipline, and employee performance